FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN BERBASIS SAKâETAP PADA UMKM - Lestari, Wahyu Sri; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study aims to examine empirically the influence of educational background, education level, business scale,business age, accounting knowledge, and information and dissemination on the quality of financial report basedon SAK ETAP on Small and Medium Micro Enterprises in Surabaya. The population of this study are all SMEsin Surabaya amounting to 40,719 MSMEs. The sampling technique used with stratified random samplingmethod, Data obtained from the distribution of questionnaires with the number of samples as many as 100 actorsUMKM. Methods of data collection using questionnaires and methods of data analysis using multiple linearregression analysis. Based on the results of data analysis and hypothesis testing, it can be concluded that theeducational background variable does not affect the quality of financial statements based on SAK ETAP whilethe level of education, business scale, business age, knowledge accounting and information and disseminationpositively affect the quality of financial statements SAK ETAP.Keywords: financial statements, SAK ETAP, small and medium micro enterprises